An initial sustainable e-learning and gamification framework for higher education - Sofiadin, Aidrina; Azuddin, Muna (IADIS Press, 2021)
The movements towards achieving sustainable goals among many countries have risen throughout the years. A part of the sustainable goals – the COVID-19 pandemic has forced many universities to move to online learning to sustain students' education. Indeed, e-learning has been delivering through the website since 1960. There is a need to develop new e-learning models that transform education to support sustainable development goals and achieve education's objectives. Interestingly, e-learning needs to integrate gamification context to increase learners' engagement and passion while promoting lifelong learning. To identify the relationship between e-learning and gamification, this paper examined and assessed various e-learning and gamification models and frameworks, specifically in sustainability, to develop an initial sustainable e-learning and gamification framework for higher education. The framework intends to assist higher education institutions in designing a gamified e-learning that promotes better learning engagement, education equity, skill development, social engagement, well-being, and lifelong learning among their learners. Thus, enabling a sustainable education throughout surviving the pandemic.